A Multi-Criteria Analysis of Russian International and Interregional Logistics Centers - Rinas V. Kashbrasiev; Anatoly M. Shihalev; Clifford Allen Lipscomb (European Regional Science Association (ERSA), 2011)
The continuous increase of marketization of the production and consumption sectors of the Russian economy requires developing logistics and distribution systems at multiple territorial scales: international, interregional, and local. Territorial organization of logistics centers is becoming an important part of Russian logistics development and increasing economic growth. The purpose of this paper is to empirically determine the optimal location of logistics centers to ensure effective international and interregional trade flows. Using 39 variables in a multi-criteria analysis of the Russian regions, including various geopolitical, economic geographical, macroeconomic, and technological criteria, this paper finds that the level of integration in the Republic of Tatarstan is much higher than the ratings of the other two Volga regions. The conclusion is that the Republic of Tatarstan has significant competitive advantages to construct an international and interregional logistics center on its territory.
Keywords: 330